2020
DOI: 10.1590/s1980-220x2018034603540
|View full text |Cite
|
Sign up to set email alerts
|

My role and responsibility: mothers’ perspectives on overload in caring for children with cancer*

Abstract: Objective: To understand the experience of maternal overload in caring for children with cancer from the mother’s perspective. Method: Symbolic Interactionism was adopted as a theoretical framework and the Grounded Theory as methodological framework. The study was conducted in a public hospital, which is reference in pediatric oncology. Data was collected from six mothers through semi-structured interviews in the second semester of 2017. Results: Mothers of children with cancer attributed meaning to the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
0
11
0
7
Order By: Relevance
“…In this study, the participating mothers reported being the main responsible for the home care provided to the children and that they remained overloaded for accompanying them in emergencies and successive hospitalizations. The literature 21 reinforces this result when analyzing six mothers of children with cancer, highlighting that the maternal burden experienced in the care of hospitalized children with cancer is the result of the accumulation of stressors resulting from care itself and the children's disease condition, especially due to the cancer diagnosis.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In this study, the participating mothers reported being the main responsible for the home care provided to the children and that they remained overloaded for accompanying them in emergencies and successive hospitalizations. The literature 21 reinforces this result when analyzing six mothers of children with cancer, highlighting that the maternal burden experienced in the care of hospitalized children with cancer is the result of the accumulation of stressors resulting from care itself and the children's disease condition, especially due to the cancer diagnosis.…”
Section: Discussionmentioning
confidence: 70%
“…The mothers' burden can be classified as physical, financial, information-related and emotional. As for the physical burden, they manifested physical fatigue related to the routine of caring for the child during hospitalization and, at home, to the demands of household chores and caring for other family members; the financial burden arising from dependence on other family members, due to job abandonment; the information-related burden on how to take care of the children, increasing the anguish and leaving them confused; and the emotional burden resulting from all the other overloads and stressors, as well as how to deal with some professionals' lack of understanding and with people's stigmas in relation to cancer 21 .…”
Section: /13mentioning
confidence: 99%
“…A sobrecarga das mães pode ser classificada em física, financeira, de informações e emocional. Quanto à sobrecarga física, elas manifestaram fadiga física relacionada à rotina de cuidados com o filho durante a hospitalização, e no domicílio, as demandas de afazeres domésticos e de cuidar de outros familiares; a sobrecarga financeira decorrente da dependência de outros membros da família, devido ao abandono do emprego; a sobrecarga de informações de como cuidar dos filhos, aumentando a angústia e as deixando confusas; e a sobrecarga emocional resultante de todas as outras sobrecargas e estressores, como também de como lidar com a falta de compreensão de alguns profissionais e com os estigmas de pessoas em relação ao câncer 21 .…”
Section: /13unclassified
“…A vida social de toda a família fica abalada, uma vez que, passeios, festas ou viagens se tornam eventos raros devido à baixa imunidade da criança com câncer. (Andrade et al, 2014) Todavia, as relações da mulher-mãe cuidadora são as que mais sofrem mudanças, pois ela fica a maior parte do tempo com o filho, e em alguns casos o acesso às redes sociais é a única forma que elas encontram para manter uma relação social (Vieira & Cunha, 2020).…”
Section: Relacionamento Interpessoal Da Mulher-mãe Cuidadoraunclassified